1996
DOI: 10.3758/bf03206836
|View full text |Cite
|
Sign up to set email alerts
|

Cortical dynamics of lateral inhibition: Visual persistence and ISI

Abstract: Psychophysical studies show that increasing the interstimulus interval (lSI) between two stimuli decreases persistence of the first stimulus. Whilesome researchers account for these results with interactions of transient and sustained inhibition, this paper describes an alternative explanation. In a neural-network model of boundary detection called the boundary contour system, persistence is the result of feedback-generated reverberations. Mechanisms to control these reverberations include lateral inhibition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…When stimuli change or move, this persistent activity would be problematic in that it could give rise to forward masking (Breitmeyer, 1980(Breitmeyer, , 1984 or to motion smear (Chen et aI., 1995). In the BCS model, such persistence can be curtailed in one of two ways: (I) by a gateddipole mechanism (Francis et aI., 1994) that, at stimulus offset, produces a reset signal inhibiting the persisting reverberatory activity or (2) by lateral inhibition operating mainly at the first competitive stage (Francis, 1996a).…”
Section: Francis's Analysis Of the Boundary Contour System Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…When stimuli change or move, this persistent activity would be problematic in that it could give rise to forward masking (Breitmeyer, 1980(Breitmeyer, , 1984 or to motion smear (Chen et aI., 1995). In the BCS model, such persistence can be curtailed in one of two ways: (I) by a gateddipole mechanism (Francis et aI., 1994) that, at stimulus offset, produces a reset signal inhibiting the persisting reverberatory activity or (2) by lateral inhibition operating mainly at the first competitive stage (Francis, 1996a).…”
Section: Francis's Analysis Of the Boundary Contour System Modelmentioning
confidence: 99%
“…According to Francis (1996aFrancis ( , 1997, the latter mechanism of lateral inhibition is the more significant contributor to the dynamics of stimulus boundary erosion over time under metacontrast conditions. Figure 5 shows schematically how the model accounts for key properties of metacontrast.…”
Section: Visual Backward Masking 1579mentioning
confidence: 99%
See 1 more Smart Citation
“…masked the flash one video frame after its presentation and found that a flash lag was still observed. Masking after 15 ms is reported to reduce visual persistence (Castet, 1994;Francis, 1996) so the fact that a flash-lag effect was still observed under these conditions can probably be legitimately interpreted as showing that greater persistence of the flash than the bar is not the cause of the flash-lag effect.…”
Section: The Persistence Hypothesismentioning
confidence: 99%
“…This sort of habituative synapse has been used to explain a variety of perceptual data that involve visual cortex (Francis, 1996a(Francis, , 1996bGrossberg, 1996a, 1996b;Francis et a!., 1994;Grossberg, 1976bGrossberg, , 1980Grossberg, , 1987Grossberg, , 1997Grunewald and Grossberg, 1996). Abbott et al (1997) have reported habituating cells in rat visual cortex and model them using (15).…”
Section: Habituative or Depressing Synapsesmentioning
confidence: 99%